Ecotels- a Way to Green Sustainable Tourism - Ankit Prakash; Vikas Sharma (International Journal of Asian Business and Management, 2023)
The global traveler's attention has shifted away from crowded cities with high-rise hotels and towards remote locations with a tranquil natural setting that doesn't harm the local ecology. Given the aforementioned information, hoteliers must immediately change their practises and trends in commercial hospitality in relation to the environment. The notion of eco hotels or green hotels has evolved as a result of growing environmental awareness. A "green hotel" is a lodging establishment that has made significant environmental improvements to its to have the least possible influence on the environment. This essay makes an effort to comprehend eco-friendly hotels, specifically the newest trends and ideal procedures. Additionally, it will make an effort to provide a summary of governmental policies and regulations with reference to hotels in India. We'll also talk about some simple tactics that hotels can use to run more environmentally friendly operations